Pertumbuhan Bayam Brasil (Alternanthera sissoo hort) secara Hidroponik dengan Pupuk Organik Cair dari Lindi Reaktor Biogas Feses Manusia - Pirade, Emeralda Rey; Kisworo, K; Madyaningrana, Kukuh (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
The slurry is one of the results of fermentation of organic material from a biogas reactor, which can be used as plant fertilizer because it is rich in macronutrients. The Brazilian spinach plant, known to contain a lot of vitamin E, is suitable for organic cultivation in a hydroponic system, which requires good fertilizer intake. This research aims to study the effect and best dose of liquid organic fertilizer from human waste-based biogas reactor leachate on the growth of Brazilian spinach (Alternanthera sissoo hort) in a hydroponic system. Six treatments were used in this study: K0 (no fertiliser), K1 (500 ppm fertiliser from AB mix), K2 (500 ppm commercial POC), P1 (250 ppm biogas reactor slurry POC), and P2 (500 ppm biogas) with 5 replications for each treatment. Brazilian spinach growth parameters measured included plant height, number of leaves, root length, wet weight, and dry weight. Plant growth parameter data were analyzed statistically using ANOVA and DMRT tests. The nutrient analysis results show that the POC macronutrient levels of human feces slurry does not meet the POC standards, according to the Ministry of Agriculture. However, giving it at a dose of 250 ppm has been proven to support the growth of Brazilian spinach plants.